RS-Seismic Processing and Web-Visualization - Pedersen, Tom Arne (UiT Norges arktiske universitet, 2014)
The University of Tromsø is conducting regular marine seismic acquisition cruises for scientific and educational purposes in the polar regions of the Norwegian Sea and beyond. Leading experts in the field currently employed by the Department of Geology at ui, have found the current seismic visualization tools lacking in several fields. The available seismic software provides a multitude of settings and filters to improve visualization, but has limitations when it comes to user friendliness, and lacks or has shortcomings for data interaction. Because of these limitations the scientists are still reverting back to using thermal paper plots for seismic data interaction. The thermal printers in the possession of UIT are old, bulky and prone to mechanical failure, and are expensive to replace. The work done in this thesis attempts to address the needs of the Department of Geology, and as a response to these needs presents the system RS. A system to process, visualize and interact with both "live" and previously recorded seismic 2D data. RS provides processing and filtering of seismic data, and presents this data in a web based user interface, using an Open Source JavaScript Tile viewer to visualize the seismic data. RS also consists of among other: a Go two tiered backend system, a custom built tile maker, web sockets for bidirectional communication and NoSQL database storage. The goal of the system is to provide a new visualization tool to replace or supplement current visualization platforms. RS does this by presenting a visualization client which can run on any device with a modern browser, giving every authorized person on a seismic vessel the ability to view and interact with seismic data. To present seismic plots to the end user, RS uses binary seismic data acquired by existing seismic software and hardware. This data is a combination of the seismic data and a variety of metadata from sensors aboard the vessel. Data is filtered for noise, and cached before images are created. These images are served by a web ...